Coaching by doing: communities of practice at Swedish sport schools in XC skiing since the 1970s - Svensson, D. (Sport in Society: Cultures, Commerce, Media, Politics, 2024)
Since the introduction of a national system for upper-secondary sport schools in Sweden in the 1970s, these institutions have been an important environment for developments in training and coaching. This is particularly true for cross-country skiing, where these schools quickly became an obligatory passage point. Coaches at the sport schools, often formally employed as PE teachers, were among the first professionalized endurance sport coaches in Sweden. This article examines how communities of practice have influenced the professionalization process of XC ski coaches at Swedish sport schools. The results show how being part of this community is conditioned on personal experience of active learning, historically as a skier yourself and currently as a coach who participates in the everyday work. The strong communities of practice have enabled coaches to maintain a high degree of self-governance and ensured that experiential knowledge remain important in relation to scientific knowledge.